Simulation of elliptical core few mode fiber switch in mode division multiplexing for enhancing bandwidth performance - Zengeni, Tendai (2023)
This study deals with designing an optical switching mechanism premised on Mode Division Multiplexing (MDM) which aims to meet the exponential increase in bandwidth capacity performance demands. MDM seeks to replace wavelength division multiplexing (WDM) technology which is currently overwhelmed capacity-wise despite being regarded as a workhorse in networking. As a result, Elliptical Core Few Mode Fiber (EC-FMF) is used to converge specific modes which depend on the refractive index changes in the core to undergo a mode conversion process for switching. This switching mechanism uses an elimination algorithm which removes unwanted modes leaving behind the ones with optimum power to propagate data. Mode dispersion limits MDM’s capability to effectively choose strong modes and EC-FMF is used to correct this. Mode conversion is the method used through Beamprop by creating other channels to transmit data from one central mode. The resultant channels are numerically optimized using Matlab, and an elimination algorithm to remove unwanted channels. Therefore, the bandwidth capacities achieved were improved by 17% compared to current switch devices. This study achieved greater bandwidth capacity namely 40 Gbps for the 2 mode EC-FMF switch, 80 Gbps for the 4 mode EC-FMF switch and 120 Gbps for the 6 mode EC-FMF switch. Bit error rate (BER) results achieved were 1.8941x10-19 for the 2 mode EC-FMF switch, 1.6867x10-17 for the 4 mode EC-FMF switch and 7.4846x10-15 for the 6 mode EC-FMF switch respectively for three simulations. This study is beneficial to practice or society as it will enable more bandwidth to be availed to users in this ever- evolving and sophisticated internet age. Furthermore, the findings of this study have extended the body of knowledge in the area of optical switching by providing a new mechanism for MDM switching applying mode conversion in conjunction with the elimination algorithm.